A social life cycle assessment methodology for additive manufacturing products - Lourenço, Francisco Manuel Parracho (2019)
The additive manufacturing technology, also known as 3D printing, is gaining popularity among the general public, the media, and in the industries. This technology is being viewed as a disruptive technology with the potential to replace many manufacturing processes and to change society as we know it. With its rapid proliferation in recent years, an understanding of the possible impacts of this technology on the stakeholders has become a crucial matter. There are many studies available in the literature concerning its economic and environmental impacts. However, research regarding the social impacts of this technology is still scarce. The main goal of this dissertation was to develop a methodology based on social life cycle assessment to measure the social impacts of an additive manufacturing product, on different stakeholders, throughout its different life cycle stages. In order to develop the methodology, six steps were adapted from the generally accepted social life cycle assessment methodology, namely: (1) Goal and scope definition; (2) Selection of stakeholder categories, subcategories and indicators for the additive manufacturing technology; (3) Definition of indicators groups; (4) Calculation method and scoring system; (5) Development of a method to aggregate the scores of the indicators and (6) Interpretation of the results. The second objective of this dissertation was to identify possible indicators that could be used in the proposed methodology to measure the social impacts of an additive manufacturing product. A list of 26 indicators has been selected from the literature. The third and last objective was to validate the 26 selected indicators, to understand if these indicators really capture the social impacts of the additive manufacturing technology. To that end, an exploratory case study was conducted in an additive manufacturing company based in England. Based on the results of the case study, 20 of the 26 indicators were validated and can be used in the proposed methodology to measure the social impacts. This study is the first to propose a methodology based on the social life cycle assessment to measure the social impacts of an additive manufacturing product, from a life cycle perspective. The proposed methodology is capable of providing a final score that quantifies the social impact of the product throughout all its life cycle stages. It also provides scores for each subcategory, stakeholder category, and life cycle stage, which facilitates the identification of hotspots that require attention by the organizations engaged in the value chain of the product. To support the implementation of the proposed methodology, a computational application model was also developed for the present study.